S-nitrosylation of the zinc finger protein SRG1 regulates plant immunity - Beimi Cui (Nature Portfolio, 2018)
Upon pathogen infection plants accumulate nitric oxide which subsequently regulates defence gene expression. Here, the authors show that S-nitrosylation of the zinc finger transcription factor SRG1 affects transcriptional suppression and contributes to activation of defence responses.